1988
DOI: 10.1111/j.1752-0606.1988.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Of Family Theory To Family Therapy*

Abstract: This paper deals with the knowledge and thinking of the therapist, who is the link between theory and therapy. Based on the self‐analysis of a single family consultation interview, the various theories employed and the decision points are described. It is suggested that therapists can espouse many theories or single ones, but are always confronted with difficult decisions. Some features of the field of family therapy which foster an overevaluation of science and certitude are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Work with “object relations” frequently involves the teaching of communication skills and pragmatic help in solving problems. Articles and presentations refer again and again to a merging of concepts across diverse orientations (Grunebaum, 1988; Watts‐Jones, 1992). We have entered an era during which the pure form practice of schools of family therapy has become a rarity.…”
mentioning
confidence: 99%
“…Work with “object relations” frequently involves the teaching of communication skills and pragmatic help in solving problems. Articles and presentations refer again and again to a merging of concepts across diverse orientations (Grunebaum, 1988; Watts‐Jones, 1992). We have entered an era during which the pure form practice of schools of family therapy has become a rarity.…”
mentioning
confidence: 99%
“…She embodies, as it were, the ethics as family therapy, much as clinicians from other fields embody the ethics of their own, respective fields. In this context, borrowing from Grunebaum (Grunebaum, 1988(Grunebaum, , 2006, the therapist herself is, in a therapeutic setting, the link between ethical theory and ethical action.…”
Section: Two Approaches To the Ethics Of Clinical Practicementioning
confidence: 99%
“…He suggested that the therapist herself is the link between knowledge and action, and went on to examine the sources of knowledge that therapists use to make decisions-many of which are inherently ethical in character-in clinical practice (Grunebaum, 1988(Grunebaum, , 2006. But if therapists make ethical decisions, what is the relevant source of knowledge?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article can be understood as an effort to go beyond a previous article (Grunebaum, 1988) in which I attempted to unpack the theories and knowledge that were the basis for the interventions I made during a fairly routine interview of a patient and his family. After the interview, the staff observing it asked why I said and did what I did, and I attempted over the next hours and weeks to answer their question.…”
Section: Introductionmentioning
confidence: 99%